The Parents Stress Level in Facing Children Study From Home in the Early of COVID-19 Pandemic in Indonesia - Ellya Susilowati; Mira Azzasyofia (GoAcademica Research & Publishing, 2020)
This research aimed to determine the stress level of parents facing children study from home at the early time of the enactment of COVID-19 social distance policy in Indonesia. The method was conducted using a survey through social media that was filled in by parents who had school-age children and were studying from home. The distribution and filling of questionnaires were conducted from March 31, 2020, to April 6, 2020. 236 respondents filled out the questionnaire, but after data cleaning processed only 223 respondents' data could be analyzed. The instrument used was the Perceived Stress Scale from Sheldon Cohen. The survey results indicate that the stress level of parents facing children study from home in the initial three weeks of social distance policy is 75.34 percent in the medium category, however there are 10.31 percent of respondents who have high-stress levels and 71.88 percent among them are women or mothers. High-stress levels are influenced, among others, by the inability of parents to guide learning, family health concerns, and family economic problems. This condition is likely to continue with the extension of the study from home period. For this reason, it is recommended that child social workers can provide online psychosocial services for parents who accompany children at home, such as family counseling, family therapy that parents and children can do, and increase family resiliency during the pandemic.